Field research 2011 - Kansas State University. Agricultural Experiment Station and Cooperative Extension Service (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2013)
Includes research reports from these locations: East Central Kansas Experiment Field, Harvey Country Experiment Field, Kansas River Valley Experiment Field, and Northwest Kansas Agricultural Research Centers.
Keywords: Kansas; Agriculture; Crops; Weed control; Disease control; Irrigation; Fertilizer